Infectious Risk of the Hospital Environment in the Center of Morocco: A Case of Care Unit Surfaces - Samira Jaouhar; Abdelhakim El Ouali Lalami; Khadija Ouarrak; Jawad Bouzid; Mohammed Maoulouaa; Khadija Bekhti (Scientifica)
Background. Equipment and hospital surfaces constitute a microbial reservoir that can contaminate hospital users and thus create an infectious risk. The aim of this work, which was carried out for the first time at a hospital in Meknes (regional hospital in the center of Morocco), is to evaluate the microbiological quality of surfaces and equipment in three potential risk areas (burn unit, operating room, and sterilization service). Methods. This study was carried out over a period of 4 months (February–May 2017). A total of 60 samples were taken by swabbing according to the standard (ISO/DIS 14698-1 (2004)) in an environment of dry area and equipment after biocleaning. Isolation and identification were performed according to conventional bacteriological methods and by microscopic observation for fungi. Results. The study showed that 40% of surface samples were contaminated after biocleaning. The burn unit recorded a percentage of 70% contamination (p value <0.001), 13% for the sterilization service, and 7% for the operating room. 89% of the isolates were identified as Gram-positive bacteria against 11% for fungi (p value <0.001). Bacterial identification showed coagulase-negative staphylococci (32%), Bacillus spp. (16%), Corynebacterium (8%), and oxidase-negative Gram-positive bacillus (40%) while fungal identification showed Aspergillus niger (n = 2) and Aspergillus nidulans (n = 1). Conclusion. To control the infectious risk related to equipment and hospital surfaces, it would be necessary to evaluate the disinfection protocol applied in these units.